Assessing Franz Boas’ ethics in his Arctic and later anthropological fieldwork - Pöhl, Friedrich (Études/Inuit/Studies, 2008)
AbstractThis paper attempts to trace Franz Boas’ ethics in his anthropological fieldwork in the Arctic and on the Northwest Coast within the scientific context of that time. In the Arctic, Boas refrained from grave robbery but “exploited his membership in the white race” and applied pressure on “his Eskimos” to secure his scientific goals. On the Northwest Coast, Boas changed his attitude: far from any ethical reflection, he and his collaborators desecrated graves for scientific and financial purposes. In many ways Boas was influenced by Kant, but in his field research Kant’s ethical position remained eclipsed; Boas’ practice in the field did not respect humans as an end in itself. Rather, Boas subscribed to an ethical utilitarianism and sustained a strong separation of science and ethics.